Economic incentives for sustainable hilsa fishing in Bangladesh: An analysis of the legal and institutional framework. (June 2016) - Islam, Md Monirul; Mohammed, Essam Yassin; Ali, Liaquat
Abstract: Bangladesh's hilsa shad ( Tenulosa ilisha ) comprises the largest single-species fishery in the country, constituting 11 per cent of the total catch and employing 2.5 million people directly or indirectly. Since 2003, following a sharp decline in catch figures, the hilsa fish has been the subject of a government conservation programme offering fishers economic incentives or payments for ecosystem services (PES). While PES schemes are widely used to conserve natural resources such as forests and watersheds, Bangladesh's programme is a rare example of PES for sustainable fishery management. Catch figures have improved since the programme was introduced; but concerns remain about fishers' socioeconomic conditions and the long-term sustainability of Bangladesh's hilsa fishery. This paper analyses the conservation scheme's legal and institutional frameworks, identifying challenges to its design and implementation, and makes recommendations to overcome them. Highlights: Hilsa fish conservation faces legal and institutional challenges in Bangladesh. The challenges include both in the design and implementation of programme. Amendment of the existing legal frameworks and legislation are needed. Proper implementation existing legal frameworks and legislation are also needed.